2014
DOI: 10.3389/fncel.2014.00265
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular gentamicin reduces the activity of connexin hemichannels and interferes with purinergic Ca2+ signaling in HeLa cells

Abstract: Gap junction channels (GJCs) and hemichannels (HCs) are composed of protein subunits termed connexins (Cxs) and are permeable to ions and small molecules. In most organs, GJCs communicate the cytoplasm of adjacent cells, while HCs communicate the intra and extracellular compartments. In this way, both channel types coordinate physiological responses of cell communities. Cx mutations explain several genetic diseases, including about 50% of autosomal recessive non-syndromic hearing loss. However, the possible in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 67 publications
0
20
1
Order By: Relevance
“…The release of ATP from HLE-B3 cells was evaluated as previously described (Figueroa et al, 2014). Briefly, cells were seeded into 60-mm diameter dishes at 70% confluence and 48 h later they were washed once with DCFS and then 500 µl of the same fresh solution were added.…”
Section: Extracellular Atp Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…The release of ATP from HLE-B3 cells was evaluated as previously described (Figueroa et al, 2014). Briefly, cells were seeded into 60-mm diameter dishes at 70% confluence and 48 h later they were washed once with DCFS and then 500 µl of the same fresh solution were added.…”
Section: Extracellular Atp Measurementmentioning
confidence: 99%
“…Previously, we have shown that LA induces opening of hemichannels formed by both Cx46 in Xenopus laevis oocytes, and by Cx43 in HeLa cells (Retamal et al, 2011;Figueroa et al, 2014). To test whether LA increases hemichannels activity in HLE-B3 cells, we determined the effects of acute exposure to this fatty acid using the Etd + uptake assay.…”
Section: Linoleic Acid Induces Hemichannels Opening In Hle-b3 Cellsmentioning
confidence: 99%
“…43 and 40.1 (ortholog of mouse Cx39) [85], suggesting that these proteins could play a relevant role in these pathological conditions. Interestingly, streptomycin has been found to reduce stretch-induced membrane permeability in mdx muscles [97] and is also known to block connexin hemichannels [98]. …”
Section: Connexins and Pannexins In Skeletal Musclementioning
confidence: 99%
“…Inhibitors of connexin-formed channels with affinities in the low-nM range are not available, but these compounds at the concentrations employed are known to inhibit HCs [80-83]. Although non-specific, divalent cations are well-known inhibitors of HCs [84]; 2) The sensitivity of growth complementation by Cx26 mutants to the inhibitory effect of Ca 2+ was altered [79].…”
Section: An Assay For Hemichannel Function In Bacteriamentioning
confidence: 99%